Opening remarks by Bernard Bett and Lian Thomas at the Kenya One Health Conference, 6-8 December 2021 - Bett, Bernard K.; Thomas, Lian F. (International Livestock Research Institute, 2021)
Kenya One Health Conference, 6-8 December 2021